Civil excavations and tunnelling [2nd ed.] a practical guide - Tatiya, Ratan (London ICE, 2017)
Civil Excavations and Tunnelling is a comprehensive guide to civil excavations at surface and subsurface levels with or without aid of explosives. It features descriptions of the latest methods, techniques, equipment, trends and practices, as well as guidance on safety and the environment.
Keywords: Tunneling; Excavation